Service quality, doctors’ communication quality and patient satisfaction in KPJ Selangor Specialist Hospital / Azura Ahmad Zahdi, Nizman Hadi Nor Hashim and Sharifah Arina Syed Mhd Hanafiah - Ahmad Zahdi, Azura (2020)
The purpose of this study is to understand the relationship between service quality, doctors’ communication quality and patient satisfaction in KPJ Selangor Specialist Hospital. A scale comprising of 21 items of service quality, 15 items of doctors’ communication quality and 9 items of patient satisfaction in a hospital were developed based on literature review. A total of 240 questionnaires were distributed to outpatients in KPJ Selangor and 222 questionnaires were collected (response rate of 92.5%). The data collected were analysed using SPSS version 23. The data analysis showed that the five dimensions of service quality (tangibles, responsiveness, reliability, assurance and empathy) is reduced into three new dimensions (Accuracy, Competency and Appeal) while doctors’ communication quality is reduced into two new dimensions (Approach and Interaction). Accuracy, Appeal and Interaction have statistically significant relationship with patient satisfaction p=0.000 (p<0.05). The new model explains 74.2% of variance in our dependent variable which is patient satisfaction. Limitations of the study include that the results of this study is only applicable to KPJ Selangor Specialist Hospital and does not reflect the situation in other KPJ Hospitals or other private healthcare providers and certainly not the public hospitals. Nonetheless, the study provides valuable insights into the patient satisfaction dimensions in a Malaysian context and how those dimensions affected patient’s overall satisfaction. Hospitals, in general, can use the study findings to measure and improve their operational performance.